Methylmalonic acid levels in serum, exosomes, and urine and its association with cblC type methylmalonic acidemia-induced cognitive impairment - Sun, Shuqi; Jin, Hong; Rong, Yu; Song, Wenqi; Li, Qiliang (Frontiers in Neurology, 2022)
Background The cblC type methylmalonic acidemia is the most common methylmalonic acidemia (MMA) in China. The biochemical characteristics of this disease include elevated methylmalonic acid and homocysteine (HCY), increased propionylcarnitine (C3), decreased free carnitine (C0). In this study, we aimed to clarify the roles of these biomarkers in cblC-MMA induced cognitive impairment and evaluate the capacity of methylmalonic acid in different fluids or exosomes to distinguish cblC-MMA induced cognitive impairment. Methods 15 non-inherited hyperhomocysteinemia (HHcy) patients, 42 cblC-MMA patients and 57 age- and sex-matched healthy children were recruited in this study. The levels of HCY were detected by an automatic immune analyzer. The levels of acylcarnitines and methylmalonic acid were detected by tandem mass spectrometer. Results The main findings were all biomarkers as HCY, acylcarnitines and methylmalonic acid had capacities for distinguishing patients with cblC-MMA induced cognitive impairment from healthy children. The methylmalonic acid in different fluids or exosomes had good performances for distinguishing patients with cblC-MMA induced cognitive impairment from HHcy patients. The methylmalonic acid in serum exosomes and neuronal-derived exosomes were able to distinguishing cblC-MMA patients with cognitive impairment from patients without cognitive impairment. The methylmalonic acid in neuronal-derived exosomes might be helpful to evaluate the severity of cblC-MMA induced cognitive impairment. Discussion Methylmalonic acid levels in serum exosomes, especially in serum neuronal-derived exosomes, serve as potential biomarkers for distinguishing cblC-MMA induced cognitive impairment.